2021
DOI: 10.1002/sctm.21-0243
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell Treatment for Perinatal Brain Injury: A Systematic Review and Meta-Analysis of Preclinical Studies

Abstract: Perinatal brain injury can lead to significant neurological and cognitive deficits and currently no therapies can regenerate the damaged brain. Neural stem cells (NSCs) have the potential to engraft and regenerate damaged brain tissue. The aim of this systematic review was to evaluate the preclinical literature to determine whether NSC administration is more effective than controls in decreasing perinatal brain injury. Controlled interventional studies of NSC therapy using animal models of perinatal brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…5 Exploratory work also suggests that neural precursor cells may be leveraged to augment innate neural repair mechanisms, which could provide potential disease-modifying options for DCP treatment. 17…”
Section: Discussionmentioning
confidence: 99%
“…5 Exploratory work also suggests that neural precursor cells may be leveraged to augment innate neural repair mechanisms, which could provide potential disease-modifying options for DCP treatment. 17…”
Section: Discussionmentioning
confidence: 99%
“…These stem cells can be either transplanted alone [12] or as part of designed engineered tissue/conduit to replace the defective neuronal tissue [13,14]. Stem cell transplantations have demonstrated positive therapeutic nerve regeneration, functional recovery, and neuronal survival in several neurological traumas such as brain injury [15] and spinal cord injury/transection [16,17], optic nerve crush [18], and injured peripheral nerves [12]. However, the use of stem cells in transplantation therapies may be limited by the small populations differentiated into neuronal cells or undesired cell proliferation or differentiation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, stem cells have several functions that might be critical to the treatment of CP including immune regulation ( Bennet et al, 2012 ), paracrine effects ( Lv et al, 2021 ), angiogenesis ( Kiasatdolatabadi et al, 2017 ), and neuroplasticity ( Jantzie et al, 2018 ). Collectively, stem cell transplantation is considered a promising therapeutic strategy in clinical practice ( Xie et al, 2020 ), and the effectiveness of stem cell transplantation in the treatment of CP has been preliminarily verified by evidence-based medicine ( Novak et al, 2016 ; Eggenberger et al, 2019 ; Xie et al, 2020 ; Smith et al, 2021 ). However, we found that stem cell treatment protocols were non-uniform across studies, and previous systematic reviews did not provide appropriate recommendations on factors that may affect the therapeutic effect, such as cell type selection, dose and administration.…”
Section: Introductionmentioning
confidence: 99%